An Application-Based Online Learning Readiness Study During The Covid-19 Pandemic (Case Study of High School / Vocational High School Students in Tangerang, Banten, Indonesia) - Dendy Jonas Managas; F Ferry; Arsi Yulianjani; Dedy Prasetya Kristiadi (IJISTECH (International Journal of Information System and Technology), 2022)
The impact of COVID-19 on learning activities in Indonesia has caused problems for students. Research that has been conducted on the failure of pedagogic delivery by teachers and difficulties in adapting to the use of technology and learning models, cannot be used as references and conclusions. The need to conduct research and literature studies becomes urgent to obtain accurate, reliable and up-to-date information. The research, which was conducted in vocational high schools and high schools in Tangerang district, was related to the readiness of students to learn about conditions during the pandemic and the learning tools used. The results of the study from this research are that there are differences in learning readiness, namely that senior high schools are more prepared than vocational schools. To find out the difference in online learning readiness, the statistical analysis used is ANOVA (analysis of Variance), the calculation uses the help of the SPSS version 20.00 application. Furthermore, this research will be a reference for education providers to innovate learning methods so that students can better participate in the learning process during the pandemic without reducing the quality of learning outcomes